IPTEKS PENGGUNAAN MODAL PADA USAHA KECIL DAN MENENGAH MENGGUNAKAN LAPORAN KEUANGAN AKUNTANSI - Lonto, Tesalonika Theresa Mutiara; Pangerapan, Sonny (Universitas Sam Ratulangi, 2018)
Small and medium enterprises are businesses run by a person / group of people to build a business. To run it you should use financial statements with an accounting information system. Because, using financial statements can find out the advantages and disadvantages of the business being run. When starting a business, we must find out the strategic place and market share that will become the place of business to run. By doing all that is needed we can do business well. Through this research, it was explained how to run a business by getting a loan from the Office of Cooperatives and Small and Medium Enterprises and ways to obtain these loans. This study also aims to find out how to run a business using financial statements with accounting information systems.Keywords: evaluating, effectiveness, grant disbursement procedure